Biosorption of Chromium(VI) and Mercury(II) from Aqueous Solutions by Eriobotrya japonica (Rosaceae) - M. Abuein, M.; M. Belazi, A. (Asian Journal of Chemistry, 2010)
A method was developed to investigate the potential removal of chromium(VI) and mercury(II) from aqueous solutions through biosorption by Eriobotrya japonica (Rosaceae). The results obtained shows removal of Cr(VI) by 68.4 % and for Hg(II) by 97.4 % for 100 mg/L solutions of Cr(VI) and Hg(II), with biomass of 3 g. However, both solutions containing Cr(VI) and Hg(II) were reached the equilibrium within 1 h. The optimum pH value used for both elements was pH 5. The biosorption of Cr(VI) and Hg(II) was studied using FTIR. The spectra suggested that the presence of Cr(VI) ions in the biomass effects the bands corresponding to the carboxyl groups. Similar result was achieved for Hg(II) ion at optimum pH 5. The results obtained by the method indicated that Eriobotrya japonica (Rosaceae) is appropriate material for biosorption of Cr(VI) and Hg(II).